Politeness in Politics - Przybysz, Jagoda (Emocje i polityka. Sceny z życia polskiego parlamentu, 2016)
The aims of this article is to analyze existing categories and forms of acts of politeness in the speeches of politicians at Polish parliament. In analysis I use visual analysis method and focus on the linguistic and cultural politeness strategies and refer to the theory of the politeness (E. Goffman, P. Brown, S. Levinson).